2002
DOI: 10.1149/1.1468646
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and Magnetic Properties of Co Thin Films Electrodeposited on Si

Abstract: The electrodeposition of thin films of the element cobalt on silicon wafers opens the possibility of producing magnetic structures on top of a technological substrate using an efficient and inexpensive method. In this paper, we present an extensive study of the electrodeposition of Co on Si͑100͒ n-type substrates. Co thin films with metallic appearance and uniform thickness were obtained at deposition rates of 0.6 ͑2.8͒ nm/s for the 26 ͑104͒ mM Co electrolyte. A strong dependence of the surface roughness on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
24
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(31 citation statements)
references
References 29 publications
7
24
0
Order By: Relevance
“…The lowest coercive field values obtained match well the data of Munford et al 59 on thick (several 100 nm) Co films electrodeposited on Si substrates. These low coercivity values can already be considered as characteristic of bulk Co with predominantly fcc structure.…”
Section: Magnetic Propertiessupporting
confidence: 88%
See 1 more Smart Citation
“…The lowest coercive field values obtained match well the data of Munford et al 59 on thick (several 100 nm) Co films electrodeposited on Si substrates. These low coercivity values can already be considered as characteristic of bulk Co with predominantly fcc structure.…”
Section: Magnetic Propertiessupporting
confidence: 88%
“…It is well-known that the H c of thin ferromagnetic layers increases roughly proportionally with the inverse of the layer thickness. 59,60 Upon having put all this together, we can now return to Fig. 3 and try to explain the continuous increase of the GMR magnitude with d Cu .…”
Section: Magnetic Propertiesmentioning
confidence: 99%
“…It was observed that the roughness was much higher when the deposition process was denominated by progressive formation of nuclei. Therefore cadmium deposited at concentration 50ppm was rougher than cadmium obtained at concentration 200 ppm because the mechanism of nucleation was progressive at low concentration, this observation had been confirm by Minford et al [53]. The roughness of cadmium was less than lead in spite of the nucleation process is a progressive type.…”
Section: Characterization Of the Depositssupporting
confidence: 59%
“…The versatility of this technique allows meticulous observations and evaluations of the textural and morphological characteristics of the films, showing better facilities than other microscopic methods [52]. Table 1 The most important parameters of AFM measurements are average roughness, root mean square roughness (Sq), surface skewness, and surface kurtosis [53]. The AFM analysis of cathode substrate shows that Sq is 0.0589 nm, i.e.…”
Section: Characterization Of the Depositsmentioning
confidence: 99%
“…Therefore, this effect also points to a large amount of APBs. It has been reported [46][47][48] that the coercive field usually decreases with increasing film thickness. This effect has been attributed to the reduced defect density for thicker films.…”
Section: Discussionmentioning
confidence: 97%